O-017 Recurrent Intracranial Vertebral Artery Dissecting Aneurysms After Stent-assisted Coil Embolization-A Computational Fluid Dynamic Analysis. (29th July 2016) - Liu, J; Jing, L; Zhang, Y; Song, Y; Wang, Y; Li, C; Wang, Y; Mu, S; Paliwal, N; Meng, H; Linfante, I; Yang, X
Abstract : Introduction: Intracranial vertebral artery dissecting aneurysms (VADAs) tend to recur despite successful stent-assisted coil embolization (SACE). Computational fluid dynamic (CFD) can assess hemodynamic alterations in wall shear stress (WSS) and velocity in the aneurysmal wall. CFD has proven to be useful in evaluating aneurysmal formation, growth and rupture. Our aim was to evaluate the hemodynamic patterns of VADA's recurrence by CFD. Materials and methods: Between September 2009 and November 2013, all consecutive patients presenting with recurrent VADAs after SACE in our institutions were enrolled in the study. Recurrence was defined as recanalization and regrowth. We assessed the hemodynamic alterations in WSS and velocity by CFD simulation after initial SACE and subsequently after retreatment of aneurysms that recurred. Results: In the study period, 112 consecutive patients with intracranial veterbrobasilar dissecting aneurysms (VBDAs) underwent endovascular treatment. Seventy-two of them were treated with SACE. Angiographic follow-up was available in 59 patients (81.9%). Recurrence was present in 10 patients (16.9%) and 6 needed retreatment. Finally, 5 patients with VADAs were included (1 was excluded because of inadequate 3D imaging). After initial treatment, three cases showed recanalization and 2 cases showed regrowth. In the 2 regrew cases, the 2 original aneurysms maintained complete occlusion, however de-novo aneurysm regrowth was confirmed near the previous site. Compared with 3 recanalised aneurysms, the completely occluded aneurysms showed high mean reductions in velocity and WSS after initial treatment (77.6% versus 57.7% in velocity, 74.2% versus 52.4% in WSS), however, remaining high WSS at region near the previous lesion where the new aneurysm originated. After the second retreatment, there was no recurrence in all cases. Compared with the 3 aneurysms that recanalised, the 4 aneurysms that maintained complete occlusion showed higher reductions in velocity (62.9%) and WSS (71.1%). Conclusion: Hemodynamics by CFD may be useful in predicting recurrence of VADAs after SACE. Disclosures: J. Liu: None. L. Jing: None. Y. Zhang: None. Y. Song: None. Y. Wang: None. C. Li: None. Y. Wang: None. S. Mu: None. N. Paliwal: 1; C; National Institutes of Health (R01 NS091075). H. Meng: 1; C; National Institutes of Health (R01 NS091075). I. Linfante: None. X. Yang: 1; C; National Natural Science Foundation of China (Grant No. 81301003, 81171079, 81371315, 81471167 and 81220108007), Special Research Project for Capital Health Development (Grant No. 2014–1-1071).